Dielectric characterizations and heating behavior of siderite in microwave field. (22nd August 2018) - Zhou, Baocheng; Zhou, Junwen; Zhang, Zimu; Hu, Tu; Yang, Li; Lin, Guo
Abstract: Microwave absorption capabilities of siderite, Fe3 O4 and Fe2 O3 were investigated by measuring the dielectric characterization (dielectric constant, loss factor and loss tangent) from room temperature to 900 °C using the microwave cylindrical resonant cavity technique at 2450 MHz. There was little change in the microwave absorption capabilities of siderite before 600 °C. As the temperature increasing, the microwave absorption capabilities of siderite increased sharply due to the generation of Fe3 O4 . However, the microwave absorption capabilities of siderite decreased when temperature higher than 900 °C, which was attributed to the formation of Fe2 O3 by the oxidation of Fe3 O4 . The microwave heating behavior of siderite was studied and the result showed that the heating rate of siderite became slower when temperature higher than 550 °C, this was because amount of decomposition reaction of siderite occurred in this stage which consuming large amounts of heat.